Qualitative research and intercultural understanding : conducting qualitative research in multicultural settings - Court, Deborah, 1950- (Routledge, 2018)
Qualitative Research and Intercultural Understanding: Conducting Qualitative Research in Multicultural Settings makes an important contribution to the fields of multiculturalism and qualitative research methods. The first section of the book is a textbook on qualitative methodology. Beginning with a sketch of the historical roots of qualitative research and its place in the research landscape, the book then explores the notion of culture and our individual and collective experiences of culture. The chapters that follow explain how to frame a study and ask qualitative research questions, how to strengthen the trustworthiness of qualitative findings and how to collect and analyze data and write a research report. This section closes with a chapter on research ethics. Every chapter is infused with the idea of researcher reflectivity in order to see beyond the researcher's personal cultural worldview. Examples of research studies are provided in every chapter, and each chapter concludes with questions and exercises for critical thought. The second section of the book is comprised of five contributed chapters in which researchers describe their own challenges in conducting research in multicultural settings. Graduate students, experienced researchers and all those interested in multiculturalism will find something to learn and enjoy in this vivid and unusual book.- Resumé vydavatel
Keywords: kvalitativní výzkum; interkulturní komunikace; multikulturalismus; qualitative research; intercultural communication; multiculturalism; učebnice vysokých škol; elektronické knihy; textbooks (higher); electronic books